Penerapan Asas Non-Diskriminasi Dalam Hak-Hak Kewarganegaraan: Tinjauan Konstitusional di Indonesia (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
The study aims to explore the application of the principle of non-discrimination in citizenship rights in Indonesia using qualitative methods based on the results of the analysis, proposing several suggestions.